Effects of the xanthine oxidase inhibitor, febuxostat, on the expression of monocyte chemoattractant protein‐1 and synchronous genes in MDCK cells treated with calcium oxalate monohydrate crystals. (3rd January 2021) - Miyazawa, Katsuhito; Nakai, Dan; Nakamura, Yuka; Tatsuno, Takanori; Inoue, Shinya; Nakazawa, Yusuke; Ishigaki, Yasuhito
Abstract : Objectives: To examine the effects of the selective xanthine oxidase inhibitor febuxostat on the expression of inflammation‐related genes involved in stone formation. Methods: Madin‐Darby canine kidney cells were exposed to febuxostat, followed by calcium oxalate monohydrate crystals. Monocyte chemoattractant protein‐1 messenger ribonucleic acid expression levels were determined by real‐time reverse transcription polymerase chain reaction analysis. Deoxyribonucleic acid microarray analysis was utilized to evaluate gene expression. Results: Calcium oxalate monohydrate crystals activated monocyte chemoattractant protein‐1 messenger ribonucleic acid expression in a time‐ and concentration‐dependent manner. Febuxostat suppressed monocyte chemoattractant protein‐1 expression. The expression levels of a group of inflammatory genes, including interleukin‐8 and chemokine (C‐X‐C motif) ligand 10, which are downstream of reactive oxygen species, fluctuated similarly to the observed monocyte chemoattractant protein‐1 fluctuations and were reduced by febuxostat pretreatment. Conclusions: Febuxostat exerts preventive effects against reactive oxygen species production and oxidative stress, and might represent a potential treatment for calcium oxalate stones. In the present study, febuxostat downregulated the calcium oxalate monohydrate crystal‐induced monocyte chemoattractant protein‐1 messenger ribonucleic acid expression.